Evaluation of a Rapid and Simplified Protocol for Direct Identification of Microorganisms From Positive Blood Cultures by Using Matrix Assisted Laser Desorption Ionization Time-of-Flight Mass Spectrometry (MALDI-TOF MS) - Dai, Yufeng; Xu, Xinyi; Yan, Xue; Li, Daming; Cao, Wei; Tang, Lingli; Hu, Min; Jiang, Chuanhao (Frontiers in Cellular and Infection Microbiology, 2021)
Early and rapid identification of microorganisms is critical for reducing the mortality rate caused by bloodstream infections (BSIs). The accuracy and feasibility of directly identifying pathogens in positive blood cultures by matrix assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) has been intensely confirmed. In this study, we combined density centrifugation and extra chemical lysis-extraction to develop an optimized method in the blood culture process, which significantly improved the effectiveness of direct identification by MALDI-TOF MS. The accuracy was evaluated by 2032 positive blood culture samples (115 species of microorganism). The overall MALDI-TOF MS based identification rate with scores ≥ 1.700 was 87.60%. 94.06% of gram-negative bacteria were identified consistently to the genus level, followed by anaerobes (93.33%), gram-positive bacteria (84.46%), and fungi (60.87%). This protocol could obtain results within 10-20 minutes at a cost of less than 0.1 per sample, which saved up to 24h in identifying 87.60% of the microorganism from positive blood cultures. This rapid and simplified protocol facilitates the direct identification of microorganism in positive blood cultures, and exhibits the advantages of cost-effective, time-saving, and easy-to-use. It could provide the causative organism of the patient to clinicians in time for targeted treatment and reduce mortality.